Catalogue of oribatid mites (Acari: Oribatida) from Continental Southeast Asia - Corpuz-Raros, Leonila; Ermilov, Sergey G. (Zootaxa, 2020)
This paper presents a catalogue of oribatid mites (Acari, Oribatida) recorded from Continental Southeast Asia (CSEA) covering a period of 55 years from 1965 to the first half of 2020. This subregion comprises countries that are located on the southeastern coast of the Asian continent, namely, Myanmar, Thailand, Laos, Cambodia and Vietnam. For each species, information is compiled on references to the original description, subsequent re-combinations of specific name with other genera, and junior synonyms used in CSEA literature, if any, as well as type habitat, habitats recorded later, and distribution within outside CSEA. A historical review of explorations and taxonomic studies in the various countries is also provided. A total of 820 valid species including subspecies and seven doubtful species are known so far from CSEA. The valid species belong to 313 genera and subgenera, 94 families and 36 superfamilies in all of the five infraorders and two hyporders of the Suborder Oribatida. The Hyporder Brachypylina is most diverse with 620 species, followed by Mixonomata (88), Enarthronota (65), Nothrina (41), Palaeosomata (5) and Parhyposomata (1). Vietnam whose fauna has been best explored tops the records with 730 species, followed by a low second by Thailand (137), then Cambodia (37) and Myanmar (11) while the oribatid fauna of Laos is still entirely unknown. Altogether, the oribatid fauna of Southeast Asia (SEA), including its two subregions, now totals 1601 species belonging to 477 genera, 109 families and 40 superfamilies. Species that are known so far only from CSEA countries and thus probably endemic is highest at 36.4% for Myanmar, 32,1% for Thailand, 23.7% for Vietnam, 0 for Cambodia, 27.2% for CSEA, 59.0% for the Malay Archipelago, and 48.7% for SEA as a whole. About 7% of the recorded species of Thailand and Vietnam are cosmopolitan or semicosmopolitan in distribution, but their faunal elements are decidedly Oriental, with about half (43–54%) occurring also in other Oriental countries. The same countries also share in common many species with other zoogeographic regions, viz. 12–14% Palaearctic, 8–16% Australian, 8–11% Neotropical, 3–11% Ethiopian, and 1–3% Nearctic.